Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/nu12072019
|View full text |Cite
|
Sign up to set email alerts
|

Banhasasim-Tang Attenuates Lipopolysaccharide-Induced Cognitive Impairment by Suppressing Neuroinflammation in Mice

Abstract: Banhasasim-tang (BHS) is an herbal medicine that has been widely used in East Asia to treat various symptoms associated with upper abdomen swelling. BHS has not been studied previously for neuroinflammation or cognitive disorder. Here, we use a lipopolysaccharide (LPS) model to investigate the effects and mechanisms of BHS in neuroinflammation and cognitive impairment of mice. We used a mouse model of LPS-induced cognitive impairment and neuroinflammation and examined whether administration of BHS prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Systemic exposure to the bacterial endotoxin, LPS, has been shown to elicit cognitive dysfunction in rodents [26] which is believed to have neuroinflammatory causes [27]. In fact, our results could thus indicate another possible mechanism to LPS-induced cognitive impairment-namely a decrease in CSF movement.…”
Section: Discussionmentioning
confidence: 63%
“…Systemic exposure to the bacterial endotoxin, LPS, has been shown to elicit cognitive dysfunction in rodents [26] which is believed to have neuroinflammatory causes [27]. In fact, our results could thus indicate another possible mechanism to LPS-induced cognitive impairment-namely a decrease in CSF movement.…”
Section: Discussionmentioning
confidence: 63%
“… 29 , 30 Moreover, BHS prevented lipopolysaccharide-induced cognitive impairment and neuroinflammation in mice. 31 The herbal medicine formulae used in this observational study demonstrated potential effects on cognitive impairment in previous animal and human studies.…”
Section: Discussionmentioning
confidence: 66%
“…BHS is used for treating dyspepsia as a traditional decoction [ 20 ]. Our previous studies showed that BHS treatment attenuates neuroinflammation and cognitive dysfunction [ 22 ]. However, the effects of BHS on oxidative stress-induced neuronal damage remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…To test spatial memory, we performed the Morris water maze (MWM) test after administration of the drug, as described previously [ 22 ]. Briefly, we trained mice in a 1.2 m diameter pool filled with white water to reach a hidden platform (10 cm diameter) for 6 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation